Role of nutritional and metabolic status on the pullet to hen transition and lifetime productivity - Noetzold, Thiago L.; Zuidhof, Martin J. (Frontiers in Physiology, 2025)
Modern poultry industry is divided into two main commercial categories: laying hens (egg-type) and broiler breeders (meat-type). They have been selected differently over the past 100 years. Despite the difference in egg production between egg- and meat-type chickens, similar physiological triggers are attributed to both during the transition from pullet to hen. In addition to the photoperiod threshold, reproduction in chickens is also connected to three main metabolic thresholds: nutrient intake, body weight (BW), and carcass composition. Much is still unknown regarding the physiological effects of these thresholds. Many differences in management and nutritional strategies have been attributed to egg- and meat-type chickens. However, not a lot of emphasis has been put on the possible physiological similarities between the main metabolic factors (body composition and nutrient intake) and thresholds (critical BW and body fat) affecting egg- and meat-type pullets during the transition to the reproduction period. Therefore, this review summarized current knowledge on the metabolic status of the pullets affecting the onset of sexual maturation, focusing on its integration with photoperiodic cues and reproductive physiology, and how the latter is affected by the metabolic status of egg- and meat-type chickens.